Interferon action: nucleolar and nucleoplasmic localization of the interferon-inducible 72-kD protein that is encoded by the Ifi 204 gene from the gene 200 cluster (The Rockefeller University Press, 1992)
The interferons are cytokines with antiviral, cell growth regulatory, and immunomodulatory activities. These activities are mediated by the proteins induced by the interferons. Earlier we described a gene cluster (the 200 cluster) consisting of at least six adjacent, interferon-activatable genes located next to the erythroid alpha- spectrin locus on murine chromosome 1. The genes of the cluster arose by repeated gene duplication and they specify proteins with pronounced sequence similarity. We have now raised polyclonal antibodies against a segment from one of these proteins (the 204 protein of 72 kD). Using these, we established that the 204 protein is a phosphoprotein whose level in cells from various murine lines can be increased up to 75-fold upon treatment with alpha interferon. Experiments involving fractionation of cell lysates and indirect immunofluorescence microscopy of control and interferon-treated cells revealed that the 204 protein is nucleolar and nucleoplasmic. This conclusion was confirmed by co-localization with B23, a known nucleolar protein. The 204 protein is the first interferon-induced protein found to be located in the nucleoli, the subcellular organelles of ribosomal RNA production and ribosome assembly. It remains to be seen whether the 204 protein affects any of these processes. Studies on 204 protein function should be facilitated by the availability of complete cDNA clones and the finding of cell lines in which the expression of this protein is impaired.